2013
DOI: 10.1093/occmed/kqt053
|View full text |Cite
|
Sign up to set email alerts
|

Family to work conflict and the usefulness of workplace support

Abstract: All forms of FWC affected work performance, including when on business travel. FWC arose from caring responsibilities but also from financial and relationship problems, which are potentially amenable to help from EAPs. Line-managers and colleagues were the primary sources of workplace support. The in-house OH service and the EAP were underutilized and they may require popularizing with employees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Peer support can be defined as "a system of giving and receiving help founded on key principles of respect, shared responsibility, and mutual agreement of what is helpful" [71]. The main support for workers within their organizations often comes from colleagues and managers [72]. Peer support at work strengthens psychological resilience by enhancing coping skills and the development of post-traumatic growth, factors which can protect workers involved in stressful situations [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…Peer support can be defined as "a system of giving and receiving help founded on key principles of respect, shared responsibility, and mutual agreement of what is helpful" [71]. The main support for workers within their organizations often comes from colleagues and managers [72]. Peer support at work strengthens psychological resilience by enhancing coping skills and the development of post-traumatic growth, factors which can protect workers involved in stressful situations [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…Research indicated that a lack of management recognition for employee effort leads to high ERI (Olejniczak and Salmon, 2014). Workplace stressors have a negative impact on staff motivation and job performance (Adaramola, 2012; Avey et al , 2012; Hancock and Page 2013; Solanki, 2013). Increased workplace stress leads to reduced productivity and performance, and increased job satisfaction leads to increased productivity and performance (Evers et al , 2014; Kobussen et al , 2014).…”
Section: Job Performancementioning
confidence: 99%
“…The main support for workers within their organizations often comes from colleagues and managers (Hancock & Page, 2013); and social support from immediate supervisors and colleagues can help decrease feelings of perceived work overload and occupational stress (Bowling et al, 2015). Consequently, peer support programs have increasingly been of interest to organizations as a way of facilitating employees’ abilities to support each other and decreasing perceived workplace stress.…”
Section: Introductionmentioning
confidence: 99%